Current development on HIV-1 protease inhibitors - Ornjira Arusksakunwong (2018)
Although a number of potent and selective inhibitors have been developed and approved as drugs for the treatment of HIV infection, efforts still needed in order to develop new inhibitors that are more potent, have unique resistance patterns, and minimal side effects. This review focuses to the HIV-1 protease (HIV-1 PR), the enzyme belongs to the family of aspartic acid based on the identification of the Asp-Thr-Gly catalytic triad. In the fast part, general features of the HIV-1 PR as well as its structure and functions were given. Afterwards, the review was targeted to discovery, characteristic, activity and emergence of drug resistant of the nine FDA (Food and Drug Administration) approval inhibitors, indinavir, saquinavir, nelfinavir, ritonavir, lopinavir, amprenavir, tipranavir, atazanavir and fosamprenavir. In addition, the two promising inhibitors (brecanavir, darunavir), which are currently under development, as well as a competitive non-peptide based inhibitors (water soluble C60 derivatives) were also introduced. © 2007 Bentham Science Publishers Ltd.